How the Islamic State rivalry pushes the Taliban to extremes - Verma, Raj (Middle East policy, 2023)
Before establishing the second Islamic Emirate of Afghanistan in August 2021, the Taliban promised they would not revert to the repressive policies and stringent interpretations of Islam they had imposed during their previous regime. However, since the US withdrawal—and despite financial incentives from the West and diplomatic pleadings within the region—the Taliban have reneged on this vow. Why have the Taliban not moderated? This article argues that their rivalry with Islamic State-Khorasan (IS-K) is the central cause. The Taliban are concerned that compromise on fundamentalism will lead their hard-line factions to break ranks and join IS-K, enhancing its reputation and allowing it to recruit more foreign fighters. This could lead to increased violence and socioeconomic and political instability in Afghanistan, undermine the legitimacy of the Taliban, and spark the collapse of the regime.